COST ANALYSIS OF BENEFITS AND ECOLOGICAL SOCIAL SYSTEM GREEN SHELL CULTIVATION IN SERANG CITY - Arwa inas shafiya; kastana sapanli (Universitas Djuanda, 2019)
Mussels are included as part of aquaculture leading commodities in Banten Province. Green mussel is one of the mussels that has been cultivated in Banten, especially in Serang City. The purposes of this research are to analyze feasibility comparison based on differences in cultivation methods, analyze connectivity of social ecological systems (SES) in green mussel cultivation, and formulate solutions to develop a good and sustainable green mussel cultivation in Serang City. The analytical methods are analysis of cost-benefit, and descriptive based on the link in the SES. The results show that stake method is more feasible based on cost-benefit analysis indicators. The problems found based on connectivity in SES subsystems of green mussel cultivation in Serang City are there is sediment that can obstruct green mussel growth on the site, disposing of garbage in the sea, conflicts between cultivators and fishermen, the coaching without further monitoring yet, no waste processing technology, and no accomodation from the city government related to cultivation components. The Recommendations that can be given are the need to dredge and study the condition of sea location, giving education about the condition of sea environmemt, doing arrangement of sea zonation rules, monitoring the implementation of coaching results, giving accomodation with guidance related to the processing of production waste, and subsidies cultivation components by the city government.Key words: analysis of cost-benefit, green mussel, marineculture, social ecological system, policy